1996
DOI: 10.3109/00498259609046688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of canthaxanthin, astaxanthin, lycopene and lutein on liver xenobiotic-metabolizing enzymes in the rat

Abstract: 1. The catalytic activities of several phase I and II xenobiotic-metabolizing enzymes and the immunochemical detection of P4501A and 2B have been investigated in liver microsomes and cytosol of male rats fed for 15 days with diets containing canthaxanthin, astaxanthin, lycopene or lutein (as lutein esters) (300 mg/kg diet) and in rats fed increasing levels (10, 30, 100 and 300 ppm) of canthaxanthin or astaxanthin in the diet. 2. Canthaxanthin increased the liver content of P450, the activities of NADH- and NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 28 publications
4
73
2
1
Order By: Relevance
“…Commencement of a high-vegetable diet, which would not be expected to increase the consumption of PCDD/Fs and PCBs, in this study caused significant increases in the blood IEQ. Numerous studies have reported that common dietary phytochemicals such as flavanoids, indoles, polyphenolics, and oxidized carotenoids possess AHR agonist activity (Gradelet et al, 1996;Heath-Pagliuso et al, 1998;Denison and Nagy, 2003;Jeuken et al, 2003;Zhang et al, 2003). Many of these natural AHR agonists have been measured in human blood in the low micromolar range (Nakagawa et al, 1997;Paganga and Rice-Evans, 1997;de Vries et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Commencement of a high-vegetable diet, which would not be expected to increase the consumption of PCDD/Fs and PCBs, in this study caused significant increases in the blood IEQ. Numerous studies have reported that common dietary phytochemicals such as flavanoids, indoles, polyphenolics, and oxidized carotenoids possess AHR agonist activity (Gradelet et al, 1996;Heath-Pagliuso et al, 1998;Denison and Nagy, 2003;Jeuken et al, 2003;Zhang et al, 2003). Many of these natural AHR agonists have been measured in human blood in the low micromolar range (Nakagawa et al, 1997;Paganga and Rice-Evans, 1997;de Vries et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have proposed reliable evidence that tryptophan and its metabolites could act as endogenous agonists at the AHR and induce AHR-regulated gene transcription both in vivo and in cultured cells [10,11]. In addition, there is evidence of a ligand-independent pathway that a variety of agents can transcriptionally activate CYP1A1, as measured by the AHR response, including hormones, omeprazole, and notably carotenoids, even though they lack the chemical characteristics typically associated with high AHR affinity [12][13][14][15][16][17][18]. However, there is no definitive explanation for the physiological function of AHR in the various tissues in which it is expressed, particularly when addressing the question of which endogenous compounds regulate AHR at physiological concentrations, the exception being tryptophan.…”
Section: Introductionmentioning
confidence: 99%
“…Such a change in BaP metabolism upon pre-or co-treatment with lycopene may result for example from an effect of lycopene on biotransformation enzymes. Lycopene intake was reported to induce ethoxyresorufin O-dealkylase and benzyloxyresorufin O-dealkylase activities in the liver (Breinholt et al, 2000) and to decrease benzyloxyresorufin O-dealkylase activity in the lungs (Jewell and O'Brien, 1999) and nitrosodimethylamine N-demethylase activity in the liver (Gradelet et al, 1996).…”
Section: Mutagenicitymentioning
confidence: 99%
“…• Gradelet et al (1996) studied the effect of various carotenoids including lycopene (5% lycopene oleoresin from tomato) on several biotransformation enzymes in the liver of male rats fed for 15 days diets containing 300 mg lycopene/ kg diet, leading to an intake of approximately 15 mg/kg body weight/day. Lycopene was reported not to induce any of the parameters measured including liver P450 content, ethoxyresorufin O-dealkylation, methoxyresorufin O-dealkylation, benzyloxyresorufin O-dealkylation, and erythromycin N-demethylation activity.…”
Section: Similarity Of Lycopene To Beta-carotenementioning
confidence: 99%
See 1 more Smart Citation